Performance evaluation of tourism supply chain management: the case of Thailand - Daraka Palang (2020)
© 2018, Emerald Publishing Limited. Purpose: The purpose of this paper is to investigate and develop a framework of the performance evaluation of tourism supply chain management (SCM) for the case of Thailand. Design/methodology/approach: The performance measurement of tourism SCM was based upon the eight dimensions of service performance, namely order process management (OPM), supplier relationship management (SRM), service performance management (SPM), capacity and resources management, customer relationship management, demand management (DM), information and technology management, tour finance supply chain. Data were collected from 195 samples of experts of each component of the supply chain to identify the weight pairwise and criteria on each tourism component. The study also adopted analytical hierarchy process (AHP) technique to rank the dimensions of service performance for searching the suitable performance measurement. Findings: The results showed that there are both similarities and differences in each tier. Among the eight dimensions subject to this measurement, OPM, SPM and SRM are ranked as 1, 2 and 3, respectively, in tourism supply chain. Research limitations/implications: One limitation should be considered. As the results of this performance measurement are drawn from sole perspectives of the tourism-business operators, these are probably different from those of the tourists. Originality/value: The contribution of this study is another effective performance measurement which is expected to benefit the evaluation of tourism supply chain for Thai tourism industry.